(untitled) (Research, Society and Development, 2022)
The virgin queens, also called "princesses", of Melipona are one of the essential physical castes that make up the society of stingless bees. In the colony or hive, they are potential reproducers that, together with the males, have the primary function of perpetuating the species in the environments where they live. Melipona eburnea has a wide geographical distribution covering Brazil, Bolivia, Colombia, Ecuador, Peru and Venezuela. In Brazil (Acre and Amazonas States), it is considered as a promising species for meliponiculture due to its productivity and easy breeding and management. Thus, the objective of this work was to perform an observational case study to know, during the rainy season, under laboratory conditions, biological and behavioral aspects of three virgin queens of this species. For this, the original colony was adapted to the observation box and then a hatchling disk was removed from it and placed under ideal conditions of temperature and relative humidity. After birth, three virgin queens were marked on the thorax, with colored and numbered labels, using non-toxic glue and placed in the colony to be accepted by the other bees. Observations were made between February and May 2005, in the morning, between 07:00 - 09:00 and between 10:00 - 12:00. We recorded that the maximum longevity or survival in the colony, without being killed or expelled, was 10 days, ranging from 8-10 days. We found that once they left the colony, they never returned. The behavioural activities performed during this period were classified into three categories: self-cleaning, mobility and immobility. Of these, the most representative was mobility, followed by immobility and self-cleaning.